Análise da cintilação ionosférica no Brasil empregando GNSS e técnicas de mineração e visualização de dados - Vani, Bruno César [UNESP] (2014)
Ionospheric scintillations are rapid variations on amplitude and/or phase of a radio signal as it passes through irregularities on electron density on the ionosphere. This phenomenum decrease the accuracy of Global Navigation Satellite Systems (GNSS) once can lead to, among other aspects, that receiver lose the lock of one or more satellites during signal tracking. The occurence and intensity of ionospheric scintillations change according to several factors like solar activity, epoch in the year, geographic location and local time. During high solar activity the e ects are more intense mainly at equatorial regions like Brazil. GNSS monitoring stations were deployed on Brazilian territory since February 2011 through projects of cooperation of several institutions of Europe and Brazil, among is inserted the Faculdade de Ciências e Tecnologia (FCT) da Universidade Estadual Paulista J ulio de Mesquita Filho (UNESP). Receivers installed at these stations provide scintillation indexes and signal metrics for each satellite tracked, so called Ionospheric Scintillation Monitor Receivers (ISMR). With the monitoring infrastructure, more than ten million monitoring observations are obtained daily. Extract relevant information in this big amount of data can be a hard process. In this context, this research investigated the usage of data mining and data visualization techniques in order to extend the possibilities of analyzing the scintillations in Brazil and its e ects on GNSS positioning.